Desenvolvimento de um colorímetro in-line para o monitoramento da extrusão de polímeros - Hamester, Letícia Sausen (2014)
This work shows the development, construction, validation and application of an in-line colorimeter used for real time color quantification of the melted flow during polymer processing in the extruder. The device uses a set of four colored LED’s, red (R), green (G), blue (B) and white (W), that intermittently and sequentially illuminate the melt flow with its intensity transmitted through the flow and quantified by a single photocell. At first the device was validated in bench using aqueous colored solutions and later in the extruder during processing, using known concentrations of the acid dye diluted in polymer. The device was able to quantify with precision and in real time the attenuation of the different wavelengths emitted by each LED, caused by the presence of chromophore groups in the melted flow. It was successful to use to monitor in real time the degradation of polypropylene submitted to multiple extrusions. Degradation was proven through off-line analyses of multiprocessed polypropylene via rheometry and spectroscopy absorption on UV-visible. It was also used to quantify color in the melted mixture of polypropylene/montmorillonite (PP/MMT) to obtain nanocomposites. Using hue and luminosity parameters of the color it was possible to follow oxidation of iron ions present as impurity in the clay structure, determining which clays were better suited to these nanocomposite production.